Analisis Optimalisasi Ketahanan Daerah Berbasis GIS, Remote Sensing dan Cloud untuk Manajemen Banjir dan Rob di Kota Semarang - Maulana, Muhammad Iqbal; Maulana, Muhammad Ilham (Jurnal Riptek, 2023)
Abstract. Floods and tidal floods are a topic of discussion every year in the city of Semarang because no proper solution has been created for mitigation. From January 2022-May 2023, most of the flood and rob events are located in flat and sloping areas. The disaster had an impact on human life, such as material, physical, economic, and psychological losses. Importance of innovation to create flood resilience is urgently needed to eliminate or minimize the adverse effects of floods and rob. Flood resilience analysis uses a spatial approach supported by GIS optimization, Remote Sensing, and the Cloud platform. Then the model builder is used to speed up and simplify the analysis process. The results of the analysis show that the highest level of flood sensitivity is in flat and gently sloping areas with high population density & buildings. Meanwhile, high capacity levels are in areas close to health facilities, have road accessibility, and have lots of economic activity. In addition, 93.37% of the area's resistance to flooding is still classified as low and medium. This should be of particular concern for areas with dense populations and buildings, such as Pedurungan District, Ngaliyan District, North Semarang District, West Semarang District, and Genuk District. Thus, through regional resilience mapping, it can become a basis for decision-making for local governments with the support of inclusive disaster management.